Case Report: Two Monochorionic Twins With a Critically Different Course of Progressive Osseous Heteroplasia - Justicia-Grande, Antonio José; Gómez-Ríal, Jose; Rivero-Calle, Irene; Pischedda, Sara; Curras-Tuala, María José; Gómez-Carballa, Alberto; Cebey-López, Miriam; Pardo-Seco, Jacobo; Méndez-Gallart, Roberto; Fernández-Seara, María José; Salas, Antonio; Martinón-Torres, Federico (Frontiers in Pediatrics, 2021)
Progressive osseous heteroplasia (POH; OMIM 166350) is a rare autosomal-dominant genetic disorder in which extra-skeletal bone forms within skin and muscle tissue. POH is one of the clinical manifestations of an inactivating mutation in the GNAS gene. GNAS gene alterations are a difficult matter to address, as GNAS alleles show genetic imprinting, produce several transcript products, and the same mutation may lead to strikingly different phenotypes. Also, most of the publications concerning POH patients are either clinical depictions of a case (or a case series), descriptions of their genetic background, or a tentative correlation of both clinical and molecular findings. Treatment for POH is rarely addressed, and POH still lacks therapeutic options. We describe a unique case of POH in two monochorionic twins, who presented an almost asymptomatic versus the severe clinical course, despite sharing the same mutation and genetic background. We also report the results of the therapeutic interventions currently available for heterotopic ossification in the patient with the severe course. This article critically supports the assumption that the POH course is strongly influenced by factors beyond genetic background but also remarks the lack of options for patients suffering an orphan disease, even after testing drugs with promising in-vitro results.